Pengaruh Kualitas Pelayanan, Kualitas Produk Terhadap Kepuasan Dan Loyalitas Pelanggan Pada Cafe Silol (Effect Of Service Quality, Product Quality On Customer Satisfaction And Loyalty In Yogyakarta Yogyakarta Silol Cafe ) - Wahyu Ajisakti Ramdhan; Ida Bagus Nyoman Udayana (EBBANK, 2022)
The purpose of this study was to determine the effect of Service Quality, Product Quality on Customer Satisfaction and Customer Loyalty (Case Study at Cafe Silol Yogyakarta Customers) This research is a quantitative research. The sample in this study is consumers who shop at Silol Cafe Yogyakarta.  Data collection was carried out using questionnaire method. The data analysis technique used is the path technique that is supported by t test and classical assumptions, the data that has been obtained are processed using SPSS 21. The results of this study indicate that Service Quality has a positive and significant effect on Customer Satisfaction, Product Quality has a positive and significant effect on Satisfaction.  Customer and Customer Satisfaction have a positive and significant effect on Customer Loyalty.